2018
DOI: 10.1097/acm.0000000000002183
|View full text |Cite
|
Sign up to set email alerts
|

Gamification in Action: Theoretical and Practical Considerations for Medical Educators

Abstract: Gamification involves the application of game design elements to traditionally nongame contexts. It is increasingly being used as an adjunct to traditional teaching strategies in medical education to engage the millennial learner and enhance adult learning. The extant literature has focused on determining whether the implementation of gamification results in better learning outcomes, leading to a dearth of research examining its theoretical underpinnings within the medical education context. The authors define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
113
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(116 citation statements)
references
References 41 publications
0
113
0
3
Order By: Relevance
“…Learn in-depth mastery of the preclinical knowledge necessary to prepare tomorrow’s doctors for the scientific advances that are rapidly changing the perspective of medical practice. Preclinical curriculum utilizes didactic lectures with practical-oriented, laboratory-based hands-on training [ 5 7 ]. However, in recent years, preclinical faculty has been facing the reduction of contact hours with the introduction of integrated curriculum and limited resources [ 5 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Learn in-depth mastery of the preclinical knowledge necessary to prepare tomorrow’s doctors for the scientific advances that are rapidly changing the perspective of medical practice. Preclinical curriculum utilizes didactic lectures with practical-oriented, laboratory-based hands-on training [ 5 7 ]. However, in recent years, preclinical faculty has been facing the reduction of contact hours with the introduction of integrated curriculum and limited resources [ 5 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of these new teaching strategies makes learning more active, student-centered, engaging, creative, effective, and enjoyable [ 8 ]. New strategies are emerging in the preclinical phase that integrates technology to make learning effective and appealing to students, [ 7 9 ], making them more relevant and applicable for remote learning during the current COVID-19 pandemic. These strategies proved very useful in the current COVID-19 crisis, and medical students appreciated synchronized online learning, especially preclinical students [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study examined the use of gamification compared with a standard online course for medical students and found that the serious game was not superior for cardiac arrest management (24). In addition, that examined the gamification literature found that focused use of gamification has the ability to increase learner engagement and enthusiasm thus aligning with learning goals (25). Finally, one study which examined the use of gamification for critical pediatric conditions including respiratory failure and supraventricular tachycardia found that gamification can improve written test scores (26).…”
Section: Discussionmentioning
confidence: 99%
“…Gamification and serious games can enhance learning by increasing learner motivation and engagement . SimWars, a well‐known national competition, uses high‐fidelity simulations scenarios to challenge resident teams on a variety of clinical cases.…”
Section: Have Residents Compete In “Wars”mentioning
confidence: 99%